The debt crisis in Poland: Causes, consequences, prospects - Tomasz Rynarzewski (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
The early seventies brought about important social and political changes in Poland. The changes were responsible for a fundamental reorientation in the conception of the strategy of socio-economic development. The aim of this strategy was the acceleration of socio-economic progress, i.e. a thorough modernisation of the Polish economy, rise of its international competitiveness and a rapid growth of consumption. These objectives were to be accomplished by a dynamic growth in the national income facilitating both the acceleration of investment rate and the absolute growth of consumption level (Diagram 1). The structure of investments was to determine a gradual restructuring of the national economy. The increasing significance of the motivating role of wages was to promote a more effective and more efficient work force. This in turn, due to the cumulating feedback, was to maintain a fast rate of national income growth.
Keywords: 330; Auslandsverschuldung; Polen